Balikpapan: Urban planning and development in anticipation of the post-oil industry era. (February 2017) - Tarigan, Ari K.M.; Samsura, D. Ary A.; Sagala, Saut; Wimbardana, Ramanditya
Abstract: Balikpapan has grown to become one of the most important cities in Indonesia, due to its oil industry. However, with the decline in oil production and the global decrease in oil prices, the city has attempted to diversify its industrial and service activity economy. This paper assesses three key factors underlying this transformation: public policies and regulations, urban infrastructure, and knowledge creation and utilisation. Future opportunities and challenges the city may face are also discussed. In the light of urban planning and development perspectives, this study can become a lesson for other cities, especially in developing countries, which some of them may overly rely on natural resources-based economy, to anticipate the transition period after an economic boom due to natural resource endowment and its price decrease. Highlights: Balikpapan has grown to become one of the most important cities in Indonesia. The city has attempted diversify its industrial and service activity economy. Three key factors underlying this transformation are discussed for the case of Balikpapan.